Every Appearance of Common Sense? Applying Pierre Bourdieu’s “Sociological Gaze” to the Profession of Librarianship - Murgu, Cal (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
This paper utilizes an ALA resolution from 2016 and the resulting arguments on an ALA public forum to analyze the profession of librarianship from a perspective informed by Pierre Bourdieu’s theories. Drawing on scholarship from sociology, organizational studies, and LIS, I argue that the concept of a profession is a form of symbolic capital working within multiple fields of power. Analyzing librarianship with this framework enables us to identify the internal and external battles being waged over control of symbolic capital within fields of power, and ask why we value “the profession” to such a degree. Within the profession, professionals, para-professionals, and managers are constantly attempting to shore up or acquire additional symbolic capital. Externally, professions are struggling to maintain their symbolic capital in relation to each other; some professions, like medicine and law, have been more adept at consecrating cultural, social and economic capital into symbolic capital. Ultimately, this approach makes clear that the concept of “a profession” is neither absolute nor neutral; it is a constructed, deeply historical socio-cultural classification system that has been embedded into our collective understanding of how labour is valued. Ultimately, bolstering support behind the notion of a “profession” might not be the most prudent course of action for librarians going forward; in fact, I’ll suggest that uncritically supporting the “profession” goes against the philosophical tenets that librarians are purported to uphold.